Exergy and environmental comparison of the end use of vehicle fuels: The Brazilian case. (August 2015) - Flórez-Orrego, Daniel; Silva, Julio A.M.; Oliveira Jr., Silvio de
Highlights: Total and non-renewable exergy costs of Brazilian transportation service are evaluated. Specific CO2 emissions of the Brazilian transportation service are determined. Overall exergy efficiency of the end use of vehicle fuels in transportation sector is calculated. A comparative extended analysis of the production and end use of transportation fuels is presented. Abstract: In this work, a comparative exergy and environmental analysis of the vehicle fuel end use is presented. This analysis comprises petroleum and natural gas derivatives (including hydrogen), biofuels (ethanol and biodiesel), and their mixtures, besides of the electricity generated in the Brazilian electricity mix, intended to be used in plug in electric vehicles. The renewable and non-renewable unit exergy costs and CO2 emission cost are proposed as suitable indicators for assessing the renewable exergy consumption intensity and the environmental impact, and for quantifying the thermodynamic performance of the transportation sector. This allows ranking the energy conversion processes along the vehicle fuels production routes and their end use, so that the best options for the transportation sector can be determined and better energy policies may be issued. It is found that if a drastic CO2 emissions abatement of the sector is pursued, a more intensive utilization of ethanol in the Brazilian transportation sector mix is advisable. However, as the overall exergy conversion efficiency of the sugar cane industry is still very low, which increases the unit exergy cost of ethanol, better production and end use technologies are required. Nonetheless, with the current scenario of a predominantly renewable Brazilian electricity mix, based on more than 80% of renewable sources, this source consolidates as the most promising energy source to reduce the large amount of greenhouse gas emissions which transportation sector is responsible for.